2008
DOI: 10.1371/journal.ppat.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Mediates Acquired Immunity to Pneumococcal Colonization

Abstract: Although anticapsular antibodies confer serotype-specific immunity to pneumococci, children increase their ability to clear colonization before these antibodies appear, suggesting involvement of other mechanisms. We previously reported that intranasal immunization of mice with pneumococci confers CD4+ T cell–dependent, antibody- and serotype-independent protection against colonization. Here we show that this immunity, rather than preventing initiation of carriage, accelerates clearance over several days, accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
492
3
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 434 publications
(539 citation statements)
references
References 54 publications
28
492
3
16
Order By: Relevance
“…It argues against a direct killing effect of the cytokine or contaminant present in the cytokine preparation. Our findings corroborate those of others showing that IL-17 potentiates in vitro neutrophil killing of pneumococcus (55). However, they are in apparent contradiction with the demonstration that IL-17 reduces neutrophil antifungal activity (56).…”
Section: Discussionsupporting
confidence: 81%
“…It argues against a direct killing effect of the cytokine or contaminant present in the cytokine preparation. Our findings corroborate those of others showing that IL-17 potentiates in vitro neutrophil killing of pneumococcus (55). However, they are in apparent contradiction with the demonstration that IL-17 reduces neutrophil antifungal activity (56).…”
Section: Discussionsupporting
confidence: 81%
“…The potential role of Articles TH17 cells in contributing to protection against repeated infection was also highlighted in a study which demonstrated that the RSV NS1protein, which acts as an interferon antagonist, specifically suppresses proliferation and activation of both CD103+CD8+ cells and TH17 cells (37). While there has been much interest in the role of IL-17 in the pathogenesis of chronic, autoimmune diseases such as rheumatoid arthritis, it also appears to have a beneficial role in acute bacterial infections such as those due to pneumococcal pneumonia (13,14). Little is known about its role in respiratory viral infections.…”
Section: Discussionmentioning
confidence: 98%
“…Data from studies involving other pulmonary pathogens such as Streptococcus pneumonia suggest that the release of interleukin (IL-17) from CD4 T cells (TH17) is extremely important in enhancing the ability of neutrophils to kill the organisms in the airways (13,14). Hence, the generation of pathogen-specific IL-17 cells may be an important component of effective secondary responses to respiratory pathogens (15).…”
mentioning
confidence: 99%
“…Once invasive disease is established, heavily encapsulated bacteria are better protected from phagocytes (22). If clearance of pneumococci from the nasopharynx is mediated by T cells (25,50), the ability of pneumococcal serotypes to persist in the nasopharynx would depend on their ability to resist killing by neutrophils (51). Heavily encapsulated serotypes were found to be more resistant to nonopsonic phagocytosis by neutrophils, and it was suggested that the structure of the capsular polysaccharide would determine the success of a serotype during nasopharyngeal carriage (51).…”
Section: Discussionmentioning
confidence: 99%